Rancang Bangun Aplikasi Pemesanan Produk Toko MUMA Berbasis Mobile - Jonathan Sinarta Surbakti; Ines Heidiani Ikasari (Teknik Informatika Universitas Pamulang, 2022)
Every E-commerce business, if they want to continue to advance and develop in its world, requires continuous updates in accordance with the times. Making a mobile-based product ordering application for MUMA stores is one way for MUMA stores to progress and develop in their business. With this mobile application, consumers will find it easy to shop for MUMA store products so that the MUMA store business becomes more developed. This research uses observation and literature study in collecting data, information and materials for research. This application will use flutter as a framework in its creation. The software testing method will use the black box method where only the functionality of the system will be tested, while testing for the objectives of this application, the data collection method through a questionnaire will be used which later the data obtained will be processed with a Likert scale calculation. Keywords: e-Commerce; Mobile Application; Flutter